2020
DOI: 10.1021/acs.jpcc.0c05287
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sulfur-Functionalized MXenes for Li-Ion Battery Applications

Abstract: The surface termination of MXenes greatly determines the electrochemical properties and ion kinetics on their surfaces. So far, hydroxyl-, oxygen-, and fluorine-terminated MXenes have been widely studied for energy storage applications. Recently, sulfur-functionalized MXene structures, which possess low diffusion barriers, have been proposed as candidate materials to enhance battery performance. We performed first-principles calculations on the structural, stability, electrochemical, and ion dynamic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Carrying out uniaxial tensile loading to investigate the mechanical properties of pristine and nanoporous graphene. An increase in system temperature results in a signicant reduction in the fracture stress and strain Siriwardane et al 140 Sulfur-functionalized MXenes Structural, stability, and ion dynamic properties…”
Section: Discussionmentioning
confidence: 99%
“…Carrying out uniaxial tensile loading to investigate the mechanical properties of pristine and nanoporous graphene. An increase in system temperature results in a signicant reduction in the fracture stress and strain Siriwardane et al 140 Sulfur-functionalized MXenes Structural, stability, and ion dynamic properties…”
Section: Discussionmentioning
confidence: 99%
“…[165] Furthermore, a recent theoretical study showed that sulphur-functionalised MXenes (Ti 2 CS 2 , V 2 CS 2 and Nb 2 CS 2 ) might provide higher gravimetric capacity than oxy-gen-terminated species (Ti 2 CO 2 , V 2 CO 2 and Nb 2 CO 2 ) for lithium storage (417.4, 404.5 and 284.4 mAh g À 1 versus 350, 335 and 250 mAh g À 1 ). [166] Specifically, the diffusion energy barrier for a single lithium ion on V 2 CS 2 (Zr 2 CS 2 ) was 0.199 eV (0.218 eV) (Figure 15 (d)), which was lower than that of V 2 CO 2 (0.24 eV) (Zr 2 CO 2 (0.5 eV)), indicating the improved ionic transport kinetics in M 2 CS 2 systems. [166][167][168] In another report, organic molecules (1-aminoanthraquinone (AQ)) were noncovalently and covalently integrated with Ti 3 C 2 T x MXenes to exploit the redox-active nature of the external species.…”
Section: Effect Of the Post-treatmentmentioning
confidence: 95%
“…[166] Specifically, the diffusion energy barrier for a single lithium ion on V 2 CS 2 (Zr 2 CS 2 ) was 0.199 eV (0.218 eV) (Figure 15 (d)), which was lower than that of V 2 CO 2 (0.24 eV) (Zr 2 CO 2 (0.5 eV)), indicating the improved ionic transport kinetics in M 2 CS 2 systems. [166][167][168] In another report, organic molecules (1-aminoanthraquinone (AQ)) were noncovalently and covalently integrated with Ti 3 C 2 T x MXenes to exploit the redox-active nature of the external species. [169] Different from noncovalent integration by mixing AQ with Ti 3 C 2 T x , covalent functionalisation was realised by diazonium reaction of MXenes with tert-butyl nitrite (Fig- ure 15 (e)), which improved the capacitance by carbonyl moieties characteristic with the two-electron redox process.…”
Section: Effect Of the Post-treatmentmentioning
confidence: 95%
See 2 more Smart Citations